In Search of Lost Iridium: Quantification of Anode Catalyst Layer Dissolution in Proton Exchange Membrane Water Electrolyzers - Milosevic, Maja; Böhm, Thomas; Körner, Andreas; Bierling, Markus; Winkelmann, Leonard; Ehelebe, Konrad; Hutzler, Andreas; Suermann, Michel; Thiele, Simon; Cherevko, Serhiy (ACS Energy Letters, 2023)
Understanding catalyst dissolution pathways in proton exchange membrane water electrolyzers is paramount for developing mitigation strategies aiming toward higher durability and lower catalyst loadings. To this end, Ir dissolution has been extensively studied using aqueous model systems but not in real devices. Aiming to bridge this knowledge gap, we use a metal-free water electrolysis setup to determine the mass balance of the dissolved Ir in an electrolyzer when applying a protocol mimicking intermittent operation. We find that the main Ir sinks are the cathode catalyst layer and the membrane, while Ir dissolution into the water lines is significantly lower. Although reproducible estimation of Ir present in the membrane is challenging, quantification of Ir within the cathode is reliable and efficient. This new finding implies that tracking Ir present in the cathode can be used to estimate anode catalyst stability, thus accelerating catalyst development and operational parameters optimization.
CRIS-Team Scopus Importer:2023-07-07